2015
DOI: 10.1097/ijg.0000000000000133
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Deformation Parameters Provided by the Corvis-ST Pachy-Tonometer in Healthy Subjects and Glaucoma Patients

Abstract: Corvis-ST precision was excellent for IOP and CCT; moderate for CDPs. Corvis-ST underestimated GAT IOP, especially at higher IOP and at lower corneal deformability levels. GAT and Corvis-ST IOP increased in thicker and less deformable corneas. Glaucoma patients showed significantly less deformable corneas than controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
89
2
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 28 publications
10
89
2
5
Order By: Relevance
“…[5][6][7]10,[14][15][16][17][18][19][20]29,32,33 Other studies have found that other baseline factors such as axial length, 21,23 age, 27 and CCT 23 also are significantly associated with corneal biomechanical parameters. To accurately understand the relationship between corneal biomechanics and ocular diseases, the effect of baseline factors on corneal deformation parameters must be clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7]10,[14][15][16][17][18][19][20]29,32,33 Other studies have found that other baseline factors such as axial length, 21,23 age, 27 and CCT 23 also are significantly associated with corneal biomechanical parameters. To accurately understand the relationship between corneal biomechanics and ocular diseases, the effect of baseline factors on corneal deformation parameters must be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…This device measures a variety of parameters such as length, area, radius, arc length, and velocity of the corneal deformation at several defined time points. Previous studies have reported significant differences between the values of the corneal deformation parameters measured with the Corvis ST in normal eyes and those in eyes with glaucoma [13][14][15][16] and keratoconus 17 and after refractive 11,18,19 and keratoplasty surgeries, 20 suggesting the potential clinical relevance of the dynamic Scheimpflug analyzer to those conditions. In addition to ocular pathologies, the corneal biomechanical parameters are associated with a range of ocular and systemic factors.…”
mentioning
confidence: 99%
“…16 Several articles have recently been published on the possible applications of the Corvis ST, particularly evaluating possible biomechanical differences in the cornea after undergoing refractive surgery procedures, [17][18][19][20][21][22] between normal and keratoconic patients, [23][24][25][26] after cross-linking, 27 and in patients with glaucoma. [28][29][30][31] However, it has been demonstrated that IOP and pachymetry have important influences on most corneal biomechanical metrics provided by both the Corvis ST and ORA. [32][33][34] It is therefore relevant to investigate the distribution and normal limits for the in vivo corneal biomechanical data derived from dynamic corneal response parameters, and determine whether these metrics have correlations with IOP and corneal thickness.…”
Section: Resultsmentioning
confidence: 99%
“…Some previously reported CST-IOP measurements were higher than the GAT-IOP measurements [710] and other studies reported that the CST-IOP was similar to [11] or was lower than [12] the GAT-IOP. Previous comparisons between the CST-IOP and GAT-IOP were controversial [712].…”
Section: Discussionmentioning
confidence: 96%